Cryptogein and capsicein promote defence responses in Quercus suber against Phytophthora cinnamomi infection - Medeira, Clara; Quartin, Virgínia; Maia, Isabel; Diniz, Inês; Matos, Mª Céu; Semedo, José Nobre; Scotti-Campos, Paula; Ramalho, José C; Pais, Isabel P; Ramos, Paula; Melo, Elvira; Leitão, António E; et al. (European Journal of Plant Pathology, 2012)
The decline of cork oak (Quercus suber) stands in Iberian Peninsula is associated with infection by Phytophthora cinnamomi. Most Phytophthora species secrete elicitins, which can enhance defence reactions against some pathogens. Here cytological and physiological effects of the elicitins cryptogein and capsicein on cork oak root infection by P. cinnamomi were evaluated. The progression of the pathogen in root tissue and its effects on total fatty acid (TFA) composition of roots and leaves were analysed in seedlings. Net photosynthesis (Pn), stomatal conductance (gs ), chlorophyll a fluorescence measurements (quantum yield of linear electron transport ϕe , photochemical quenching qP, non-photochemical quenching NPQ) and carotenoid determinations were carried out in well established (4 months) plants. In elicitin-treated roots, 2 days after inoculation, the pathogen which presented loss of viability and membrane degradation was mainly restricted to the intercellular spaces of the cortical parenchyma, and did not reach the vascular cylinder. Electron dense materials accumulated in the intercellular spaces of the cortex next to disorganized hyphae, suggested to be related with defence reactions. Cryptogein (or its interaction with P. cinnamomi) induced enhanced lipid synthesis in leaves, which may contribute to preserve membrane stability. P. cinnamomi decreased Pn , gs , ϕe , and qP, whereas elicitintreated plants displayed values similar to controls. Overall, the results indicated a resistance response of cork oak against this oomycete, induced by the elicitins.
Keywords: cytology; decline disease; fluorescence; leaf gas exchanges; Membrane Lipids; photosynthetic pigments

Linear Aliphatic Dimeric Esters from Cork Suberin - Graça, José; Santos, Sara (Biomacromolecules, 2006)
Cork suberin was partially depolymerized by methanolysis catalyzed by calcium hydroxide. Analysis by GC-MS of the methanolysate showed suberin monomers, including glycerol and long-chain α,?-diacids and ?-hydroxyacids. ESI-MS analysis of the methanolysate showed, besides the aliphatic monomers, suberin oligomers, including linear dimeric esters of α,?-diacids and ?-hydroxyacids. Two types of dimeric esters were identified:? a α,?-diacid linked to a ?-hydroxyacid and two inter-linked ?-hydroxyacids. The α,?-diacids and ?-hydroxyacids found as monomer residues in the dimeric esters were mainly the C18 monomers with midchain substituents. The identification of these dimeric esters was based in their CID-MS/MS spectra and confirmed after synthesis of model compounds. The occurrence of inter-esterified long-chain monomers in suberin brings a new insight in the understanding of the polyester structure of this biopolymer.
From Duplicate 1 (Linear Aliphatic Dimeric Esters from Cork Suberin - Graça, José; Santos, Sara)
Keywords: cork suberin; dimeric esters; Dimerization; Electrospray Ionization; Electrospray Ionization: metho; Esters; Esters: chemistry; GC-MS (voyant); Lipids; Mass; Membrane Lipids; Membrane Lipids: chemistry; Molecular Structure; Sensitivity and Specificity; Spectrometry; Trees; Trees: chemistry

Antimutagenicity of a suberin extract from Quercus suber cork. - Krizková, L; Lopes, M H; Polónyi, J; Belicová, a; Dobias, J; Ebringer, L (Mutation research, 1999)
The possible protective effect of a suberin extract from Quercus suber cork on acridine orange (AO)-, ofloxacin- and UV radiation-induced mutagenicity (bleaching activity) in Euglena gracilis was examined. To our knowledge, the present results are the first attempt to analyse suberin in relation to mutagenicity of some chemicals. Suberin exhibits a significant dose-dependent protective effect against AO-induced mutagenicity and the concentration of 500 micrograms/ml completely eliminates the Euglena-bleaching activity of AO. The mutagenicity of ofloxacin is also significantly reduced in the presence of suberin (125, 250 and 500 micrograms/ml). However, the moderate protective effect of suberin on UV radiation-induced mutagenicity was observed only at concentrations 500 and 1000 micrograms/ml. Our data shows that suberin extract from Q. suber cork possess antimutagenic properties and can be included in the group of natural antimutagens acting in a desmutagenic manner.
Keywords: Acridine Orange; Acridine Orange: toxicity; Animals; Antimutagenic Agents; Antimutagenic Agents: pharmacology; Euglena gracilis; Euglena gracilis: drug effects; Euglena gracilis: genetics; Euglena gracilis: radiation effects; Lipids; Membrane Lipids; Membrane Lipids: pharmacology; Mutagenicity Tests; Mutagenicity Tests: methods; Mutagens; Mutagens: toxicity; Ofloxacin; Ofloxacin: toxicity; Plant Extracts; Plant Extracts: pharmacology; Plant Shoots; Plant Shoots: chemistry; Spectrophotometry, Ultraviolet; Superoxides; Superoxides: metabolism; Trees; Trees: chemistry; Ultraviolet Rays

13C solid-state nuclear magnetic resonance and Fourier transform infrared studies of the thermal decomposition of cork. - Pascoal Neto, C.; Rocha, J.; Gil, A.; Cordeiro, N.; Esculcas, a P.; Rocha, S.; Delgadillo, I.; de Jesus, J. D.; Correia, a J. (Solid state nuclear magnetic resonance, 1995)
The thermal decomposition of cork has been studied by Fourier transform infrared (FTIR) spectroscopy and 13C solid-state nuclear magnetic resonance (NMR) spectroscopy with cross-polarization and magic-angle spinning (CP-MAS), high-power 1H decoupling (HPDEC) and cross-polarization depolarization-polarization (CPDP). Waxes and other soluble components of cork begin to decompose at ca. 150 degrees C. This is accompanied by partial decomposition of suberin, probably initiated at the points of attachment to the cell wall. The carbohydrates begin to decompose at ca. 200 degrees C. The decomposition of lignin begins at 250-300 degrees C, while suberin undergoes further degradation. Significant amounts of coke are formed in the process. At 400 degrees C cork has been transformed into coke with traces of partially decomposed suberin. The thermal decomposition of cork is dependent on the calcination time, particularly in the 200-350 degrees C range.
The following values have no corresponding Zotero field: accession-num: 7773647
Keywords: Fourier Transform Infrared (citation); Hot Temperature; Lignin; Lignin: chemistry; Lipids; Magnetic Resonance Spectroscopy; Membrane Lipids; Membrane Lipids: chemistry; Polysaccharides; Polysaccharides: chemistry; Spectroscopy